Adapting African Agriculture to Climate Change : Transforming Rural Livelihoods - Leal Filho, Walter; Esilaba, Anthony O.; Rao, Karuturi P.C; Sridhar, Gummadi (Climate Change Management, 2015)
This book summarizes the evidence from different African countries about the local impacts of climate change, and how farmers are coping with current climate risks. The different contributors show how agricultural systems in developing countries are affected by climate changes and how communities prepare and adapt to these changes.